Realmente Tenemos la Capacidad: Engaging Youth to Explore Health in the Dominican Republic Through Photovoice - Catalina Tang Yan; Arelis Moore de Peralta; Edmond P. Bowers; Linda Sprague Martinez (The University of Alabama, 2022)
Youth are often at risk for physical and psychosocial illnesses, and yet their input is rarely included in health assessments and interventions. Two U.S.-based universities partnered with community stakeholders and youth in Las Malvinas II, Dominican Republic to explore factors that promote and/or hinder the health of youth in Las Malvinas II. Youth (n=8) conducted a photovoice, and identified six key health priorities: (1) good nutrition, (2) depression and poverty, (3) violence, (4) sports and neighborhood association, (5) education, and (6) sanitation and community infrastructure. Findings revealed youth's exploration of complex multi-level determinants of health. This study suggests youth have nuanced understanding in regards to health. This paper presents the findings of the photovoice led by the youth as an illustrative case study of using CBPR-based methodologies to engage youth in local community health improvement efforts in Las Malvinas II, Dominican Republic.